Catalytic properties of hydroperoxide lyase from potato seedlings - Kopich, V.M.; Kharchenko, O.V. (Reports of the National Academy of Sciences of Ukraine, 2015)
Catalytic properties of hydroperoxide lyase (HPL) from potato seedlings are studied. HPL was extracted from potato seedlings and purified by centrifugation, solubilization with detergent, ammonium sulfate precipitation, and ion-exchange chromatography. pH 6.3 and 6.5 were optimum for the lysis of 9-hydroperoxy-linoleic acid and 13-hydroperoxy-linoleic acid substrates, respectively. The substrate specificity of the DEAE-Toyopearl-purified HPL was determined by examining the activities of the HPL with 9-hydroperoxy-linoleic acid, 9-hydroperoxy-linoleic alcohol and 13-hydroperoxy-linoleic acid. Apparent KM values for 9-hydroperoxy-linoleic acid and 13-hydroperoxy-linoleic acid were 3.92 and 6.31 μM. Corresponding Vmax values were 5.54 and 1.94 μM/min. 9-hydroperoxy-linoleic alcohol inhibits HPL with an IC50 of 20 μM. Phosphatidic acid inhibits HPL by about 40% at 50 μM, indicating a role of this phospholipid in the maintenance of cellular levels of lipid hydroperoxides.